Determinan Kepuasan Pelanggan KPR di BNI Syariah Kantor Cabang Surabaya Dharmawangsa - Prabowo, Prayudi Setiawan; Bella Halimatus (Universitas Negeri Surabaya, 2019)
This study aims to examine the influence of determinant of KPR customer satisfaction in BNI Syariah Surabaya Dharmawangsa Branch Office. The number of samples used in this study amounted to 40 respondents who came from KPR customers at BNI Syariah Surabaya Dharmawangsa Branch Office and used probability sampling techniques. This study uses a multiple linear regression analysis tool. The results showed that partially the service quality and price variables had a significant effect on customer satisfaction variables while the product quality, emotional and cost variables did not significantly influence the customer satisfaction variable.